Theorizing Graphic Embodiments: A Feminist Perspective - Lisa DeTora; Jeannie Ludlow (Humanities)
In response to the increasing politicization and polarization of discourses around gender, sexuality, and the body, feminist theorists like Judith Butler call for feminism to strive toward flexibility and responsivity. This essay lays out some of the theoretical considerations that inform studies of graphic embodiment—or studies of embodiment in graphic narratives—both generally and within feminist studies, then examines several graphic texts by Tillie Walden and Élodie Durand that exemplify feminist theories of embodiment, with particular attention to the creative co-construction of embodied narratives.